2014
DOI: 10.1007/s12032-014-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog signaling may promote invasion and metastasis of oral squamous cell carcinoma by activating MMP-9 and E-cadherin expression

Abstract: The aim of this study was to investigate sonic hedgehog (SHH) signaling pathway components (Shh and Gli-1), E-cadherin, and MMP-9 expression in human oral squamous cell carcinoma (OSCC) and to evaluate their role in prognosis. Expression of Shh, Gli-1, and MMP-9 was significantly upregulated in 74 OSCC samples compared with non-cancerous tissue samples (Shh IOD: 162.44 ± 29.35 and 608.82 ± 170.99; Gli-1 IOD: 203.50 ± 71.57 and 831.11 ± 242.352; MMP-9 IOD: 196.69 ± 64.48 and 721.64 ± 197.99 in non-cancerous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 35 publications
8
57
0
2
Order By: Relevance
“…The expression of MMP-2 and MMP-9 may be regulated by Hh pathways (32)(33)(34). Our results demonstrated that deguelin was capable of modulating migration and invasion in PC cells by regulating the expression of MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 59%
“…The expression of MMP-2 and MMP-9 may be regulated by Hh pathways (32)(33)(34). Our results demonstrated that deguelin was capable of modulating migration and invasion in PC cells by regulating the expression of MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies suggested additional effects of Shh signaling on metastasis and CSCs besides its function in promoting cancer cell proliferation (34)(35)(36). Upregulated Shh signaling was found to facilitate metastasis and to be associated with poor prognosis in various types of cancer, possibly due to its role in regulating stemness of CSCs, which remains to be fully elucidated (37).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, there are reports of canonical and non-canonical Hh signaling in other tumor types, such as breast, lung, prostate, and colon, where Hh signaling is not the driving mutation but is involved in tumor progression and contributes to treatment failure and tumor recurrence [13, 33]. There have also been several published findings on Hh signaling in OSCC, where it is known that Hh signaling contributes to growth, migration and invasion [34, 35]. In our system, OSCC signals through both canonical and non-canonical Hh signaling to increase Gli2 activation and expression of downstream target genes.…”
Section: Discussionmentioning
confidence: 99%